The pacing and tempo of running in the analysis of the performances of the top hurdlers at the Olympic Games in Paris - Ogandzhanov, A. L.; Samoylov, G. V.; Salamatov, M. B.; Larin, A. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to pinpoint the crucial kinematic metrics that contribute to the success of the world's top male hurdlers in the 110-meter hurdles, we conducted a thorough examination of their performances at the Olympic Games in Paris.